Remarks on Almost Cosymplectic 3-Manifolds with RICCI Operators - Quanxiang Pan; Yajie Wang (Journal of Mathematics)
Let M be an almost cosymplectic 3-h-a-manifold. In this paper, we prove that the Ricci operator of M is transversely Killing if and only if M is locally isometric to a product space of an open interval and a surface of constant Gauss curvature, or a unimodular Lie group equipped with a left invariant almost cosymplectic structure. Some corollaries of this result and some examples illustrating main results are given.